Student, Faculty, and Staff Approval of University Smoke/Tobacco-Free Policies: An Analysis of Campus Newspaper Articles. (20th March 2018) - Seitz, Christopher M; Kabir, Zubair; Greiner, Birgit A; Davoren, Martin P
Objective: To provide a nontraditional source of data to university policymakers regarding student, faculty, and staff approval of university smoke/tobacco-free policies, as published through campus newspaper articles. Methods: From January to April 2016, a total of 2523 articles were retrieved concerning campus smoking/tobacco at 4-year, public universities. Of these, 54 articles met the inclusion factors, which described 30 surveys about campus approval of tobacco-free policies and 24 surveys about smoke-free policies. Results: In all, the surveys included more than 130 000 respondents. With the exception of 4 surveys, all reported that the most of the respondents approved a tobacco/smoke-free campus policy. Conclusions: Although the study had several limitations, the findings provide a synthesis from a nontraditional data source that is consistent with findings from the peer-reviewed literature, in which most of the students, faculty, and staff on university campuses approve of smoke/tobacco-free campus policies.